2014
DOI: 10.1155/2014/938272
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Silver and Gold Nanoparticles Using Aqueous Extract of Seaweed,Turbinaria conoides,and Their Antimicrofouling Activity

Abstract: Silver and gold nanoparticles were synthesized using an aqueous extract of the seaweed Turbinaria conoides and their antibiofilm activity against marine biofilm forming bacteria is reported here. The UV-Vis spectra showed the characteristics SPR absorption band for Ag NPs at 421 and for Au NPs at 538 nm. Further, the synthesized nanoparticles were characterized using FT-IR, XRD, FESEM, EDX, and HRTEM analysis. Spherical and triangular nanostructures of the Ag and Au nanoparticles were observed between the size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
72
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(82 citation statements)
references
References 47 publications
(45 reference statements)
8
72
0
2
Order By: Relevance
“…In the present study, LC 50 value of the synthesized AgNPs was calculated to be 163 g/mL. In accordance with the present study, Vijayan et al [37] reported 50% mortality of brine shrimp nauplii at 88.91 g/mL concentration of AgNPs synthesized from seaweed Turbinaria conoides, which was a more toxic compound compared to our synthesized AgNPs. Therefore, the biosynthesized V. vinifera mediated AgNPs can definitely be used as an ecofriendly antibacterial and anticancer agent in food and pharmaceutical industries.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, LC 50 value of the synthesized AgNPs was calculated to be 163 g/mL. In accordance with the present study, Vijayan et al [37] reported 50% mortality of brine shrimp nauplii at 88.91 g/mL concentration of AgNPs synthesized from seaweed Turbinaria conoides, which was a more toxic compound compared to our synthesized AgNPs. Therefore, the biosynthesized V. vinifera mediated AgNPs can definitely be used as an ecofriendly antibacterial and anticancer agent in food and pharmaceutical industries.…”
Section: Discussionsupporting
confidence: 90%
“…On another front, Ramkumar Vijayan et al have used an aqueous solution containing an extract taken from Turbinaria conoides to biosynthesize both Ag and Au nanoparticles. Their study also investigated the antibiological film formation activity of the nanoparticles against marine biofilm forming bacteria [115]. Also, studies into antimicrobial agents have found that AgCl nanoparticles biosynthesized using an aqueous extract containing Sargassum plagiophyllum were effective agents against bacterial pathogens such as Escherichia coli [116].…”
Section: Silver (Ag) Nanoparticlesmentioning
confidence: 99%
“…Their study also investigated the anti biological film formation activity of the nanoparticles against marine biofilm forming bacteria. Also, studies into antimicrobial agents have found that AgCl nanoparticles biosynthesized using an aqueous extract containing Sargassumplagiophyllum were effective agents against bacterial pathogens such as Escherichia coli [41].…”
Section: Silver (Ag) Nanoparticlesmentioning
confidence: 99%